Fairness considerations in joint venture formation - Hossain, Tanjim; Lyons, Elizabeth; Siow, Aloysius (Experimental economics : a journal of the Economic Science Association, 2020)
Using a series of laboratory experiments in the context of bilateral bargaining over whether and how to engage in a joint venture, this paper shows that fairness concerns result in failures to undertake profitable joint production opportunities. We find that framing an opportunity as an employment relationship rather than as a partnership significantly reduces these inefficiencies and increases subjects’ welfare. Consistent with the theoretical model developed in the paper, text analysis and a follow-up experiment demonstrate that the lower likelihood of an efficient outcome in the partnership frame is driven primarily by a concern for fairness generated by the perceived social relationship associated with partnerships, and not by differences in the economic structure, cognition, subject motivation, or changes in relative bargaining power.